Sosialisasi Digital Marketing sebagai Media Informasi Pengembangan Bisnis UMKM menuju Era Society 5.0 - Nurwaida, An-Nisa Aina; Hendri, Hendri Julian Pramana; Permana, Ilham (Jurnal AbdiMU (Pengabdian kepada Masyarakat), 2025)
Micro, Small and Medium Enterprises (MSMEs) are one of the businesses that are always consistent and growing, bringing a major contribution in driving national economic growth. On the other hand, the development of technology and digital media should be part of self-development investment to accelerate this growth. However, the use of digital technology such as Digial Marketing is still unable to be optimized by MSME players. This community service activity aims to increase the understanding and skills of MSME players in Sukamulya Village, Singajaya District, Garut Regency in utilizing digital media as a means of marketing products. The method used is the Asset Based Community Development (ABCD) approach through three main stages, including (1) observation and interviews, (2) lectures and discussions, and (3) demonstrations and practices in using social media such as Whatsapp Business, Instagram and E-Commerce. The results of this activity showed an increase in participants' enthusiasm and understanding of the concept of Digital Marketing.  Participants understand the potential and appropriate use of social media for product publication needs, expanding market reach and business scale development. This activity is expected to be the beginning of a sustainable program in shaping MSME actors who are more productive and adaptive to technological developments in the Society 5.0 era.